english: english - Permatasari, Yofi; Silalahi, Wilma (Journal of Business, Management, and Social Studies, 2025)
This research aims to explore and find out the validity of electronic buying and selling agreements in Indonesian civil law based on the perspective of Law of Obligation. In this research, the study uses a normative research method that relies on the analysis of laws and regulations as primary sources, supported by doctrine or opinions of legal experts as secondary sources. The results obtained are that electronic buying and selling agreements in civil law based on the law of obligation are valid and regulated in Article 1320 of the Civil Code and the Law on Information and Electronic Transactions. The parties also get legal protection if they suffer losses preventively and repressively. The novelty in this research is because of the merging of two things, namely buying and selling that is usually done offline is now done online and scientific research needs to be done.